2021
DOI: 10.1021/acssuschemeng.1c07482
|View full text |Cite
|
Sign up to set email alerts
|

Engineering the Electronic Structure of NiFe Layered Double Hydroxide Nanosheet Array by Implanting Cationic Vacancies for Efficient Electrochemical Conversion of 5-Hydroxymethylfurfural to 2,5-Furandicarboxylic Acid

Abstract: The utilization of biomass resources is essential for constructing a carbon neutral society. Electrochemical conversion of biomass-derived platform molecule 5-hydroxymethylfurfural (HMF) to 5-furandicarboxylic acid (FDCA) is a highly promising alternative pathway for the production of valuable biobased oxygenated chemicals, which primarily takes advantage of the ongoing development of efficient, robust, and inexpensive catalysts. In the present work, a carbon paper-supported nickel-iron layered double hydroxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 66 publications
2
24
0
Order By: Relevance
“…(A) Polarization curves of V o ‐NiO, NiO, and Ni plate; (B) 5‐hydroxymethylfurfural (HMF) adsorption energy of V o ‐NiO, and NiO 78 ; (C) volcanic plot of HMF electrooxidation on TMOs 79 ; (D) schematic illustration and linear voltammetry scanning (LSV) curves of HMF oxidation over catalysts 83 ; (E) the capacitive current densities for HMF oxidation reaction (HMFOR) of Co 0.4 NiS@NF and Ni 3 S 2 @NF; (F) the FE and selectivity of 2,5‐furandicarboxylic acid (FDCA), and the conversion of HMF obtained by the Co 0.4 NiS@NF for 11 consecutive cycles of HMFOR; (G) oxygen evolution reaction (OER) (1.0 M KOH) and half‐way injected HMF (10 × 10 −3 M HMF) under 1.45 V 84 ; (H) TEM images of the 5.2%Ce–CoP nanosheets; (I) HRTEM image of the 5.2%Ce–CoP nanosheets (the yellow circles indicate lattice defects and deformations); (J) the two‐dimensional charge difference isosurface of 5.2%Ce–CoP (red: electron‐rich area, blue: deficient area) 85 ; source : (A and B) Copyright 2022, Elsevier; (C) Copyright 2022, Elsevier; (D) Copyright 2022, American Chemical Society; (E–G) Copyright 2022, Wiley; (H–J) Copyright 2022, the Royal Society of Chemistry…”
Section: Design Strategies For Electrocatalystsmentioning
confidence: 99%
See 2 more Smart Citations
“…(A) Polarization curves of V o ‐NiO, NiO, and Ni plate; (B) 5‐hydroxymethylfurfural (HMF) adsorption energy of V o ‐NiO, and NiO 78 ; (C) volcanic plot of HMF electrooxidation on TMOs 79 ; (D) schematic illustration and linear voltammetry scanning (LSV) curves of HMF oxidation over catalysts 83 ; (E) the capacitive current densities for HMF oxidation reaction (HMFOR) of Co 0.4 NiS@NF and Ni 3 S 2 @NF; (F) the FE and selectivity of 2,5‐furandicarboxylic acid (FDCA), and the conversion of HMF obtained by the Co 0.4 NiS@NF for 11 consecutive cycles of HMFOR; (G) oxygen evolution reaction (OER) (1.0 M KOH) and half‐way injected HMF (10 × 10 −3 M HMF) under 1.45 V 84 ; (H) TEM images of the 5.2%Ce–CoP nanosheets; (I) HRTEM image of the 5.2%Ce–CoP nanosheets (the yellow circles indicate lattice defects and deformations); (J) the two‐dimensional charge difference isosurface of 5.2%Ce–CoP (red: electron‐rich area, blue: deficient area) 85 ; source : (A and B) Copyright 2022, Elsevier; (C) Copyright 2022, Elsevier; (D) Copyright 2022, American Chemical Society; (E–G) Copyright 2022, Wiley; (H–J) Copyright 2022, the Royal Society of Chemistry…”
Section: Design Strategies For Electrocatalystsmentioning
confidence: 99%
“…For example, Wang et al. successfully prepared carbon paper–supported NiFe‐layered double hydroxide (LDH) rich in cation defects (d‐NiFe LDH/CP) for catalytic HMF oxidation to FDCA via hydrothermal and alkaline etching methods 83 . Characterization results showed that the electron density of d‐NiFe LDH could be effectively increased by the implantation of cationic vacancies, which was beneficial to improve the electrocatalytic performance (Figure 6D).…”
Section: Design Strategies For Electrocatalystsmentioning
confidence: 99%
See 1 more Smart Citation
“…22−24 The pioneering work of Grabowski and his colleagues in 1991 demonstrated the selective HMF oxidation electrocatalyzed by nickel oxide/hydroxide, leading to the production of FDCA with 71% yield. 25 Over the past decades, various transitionmetal-based electrocatalysts have been developed as efficient alternatives to selectively produce FDCA, owing to their prominent catalytic performance, stability, low cost, as well as environmental friendship. 26−29 However, most of the developed electrocatalysts have been exclusively dedicated to accelerate anodic oxidation of HMF, and the use of distinct catalysts is highly required to pair the hydrogen evolution reaction (HER) on the cathode with the HMF electrooxidation reaction (HMFOR) on the anode, which would bring about manipulative complexity and cost issues.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In the search for a suitable anode reaction, we noticed that water-soluble 5-hydroxymet hylfurfural (HMF) produced by glucose (a downstream product of lignin biomass [3]) dehydration [4] could be selectively oxidized to 2,5-furandicarboxylic acid (FDCA). As a crucial renewable polymer monomer to replace petroleum-based terephthalic acid, FDCA might polymerize into poly(ethylene 2,5-furandicarboxylate) (PEF), which is regarded as a substitute for petroleum-based polyethylene terephthalate (PET) [5].…”
Section: Introductionmentioning
confidence: 99%